2011
DOI: 10.1016/j.yfrne.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of pair bonding: Insights from a socially monogamous rodent

Abstract: The formation of enduring relationships between adult mates (i.e., pair bonds) is an integral aspect of human social behavior and has been implicated in both physical and psychological health. However, due to the inherent complexity of these bonds and the relative rarity with which they are formed in other mammalian species, we know surprisingly little about their underlying neurobiology. Over the past few decades, the prairie vole (Microtus ochrogaster) has emerged as an animal model of pair bonding. Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
296
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(305 citation statements)
references
References 253 publications
(436 reference statements)
5
296
2
2
Order By: Relevance
“…For example, activation of OTRs, but not V1aRs, is necessary for the establishment of pair bonds in zebra finches, with much stronger effects in females (16,19,26). Similarly, pair bonding in female prairie voles is more strongly dependent on OTR activation than on V1aR activation, whereas the converse is true for males (27). The basis for these sex differences is not clear, but recent experiments in zebra finches have demonstrated that socially induced Fos activity of VP and OT neurons varies in relation to sex, social context, and personality (28).…”
Section: Pvn Ot Neurons Promote Pair Bonding and Intrapair Affiliationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, activation of OTRs, but not V1aRs, is necessary for the establishment of pair bonds in zebra finches, with much stronger effects in females (16,19,26). Similarly, pair bonding in female prairie voles is more strongly dependent on OTR activation than on V1aR activation, whereas the converse is true for males (27). The basis for these sex differences is not clear, but recent experiments in zebra finches have demonstrated that socially induced Fos activity of VP and OT neurons varies in relation to sex, social context, and personality (28).…”
Section: Pvn Ot Neurons Promote Pair Bonding and Intrapair Affiliationmentioning
confidence: 99%
“…Thus, the sex differences in peptide function may derive from sexually differentiated patterns of neuronal activation. To date, experiments in voles have focused most extensively on nonapeptide receptors in the nucleus accumbens, ventral pallidum, and lateral septum (LS) (27). These brain regions receive direct input from several cell groups, including the SON, PVN, and medial extended amygdala (including the BSTm) (29,30), yet it is unclear which of these cell groups are relevant to pair bonding, and whether paracrine modulation from other cell groups plays a role.…”
Section: Pvn Ot Neurons Promote Pair Bonding and Intrapair Affiliationmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of oxytocin, vasopressin, dopamine, and CRF in social cognition have been explored using the partner preference test (PPT) as a laboratory proxy for pair bond formation (Lim et al, 2004(Lim et al, , 2007Curtis et al, 2006;Aragona and Wang, 2009;Ross and Young, 2009). This research has led to neuroanatomical models for the formation of mating-induced partner preferences (Young and Wang, 2004;Young et al, 2011). These findings in voles have also led to insights into human social cognition that are relevant to social deficit disorders, such as autism and schizophrenia (Hammock and Young, 2006;McGraw and Young, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous disciplines have contributed to the copious studies indicating a role for oxytocin and vasopressin systems in adult social behavior (for detailed reviews, see Carter et al, 2008;Donaldson and Young, 2008;Insel, 2010;Gordon et al, 2011;Kavaliers and Choleris, 2011;MeyerLindenberg et al, 2011;Young et al, 2011;Albers, 2012;Bosch and Neumann, 2012;Ebstein et al, 2012;Wacker and Ludwig, 2012;Zink and Meyer-Lindenberg, 2012;Goodson, 2013). We know that manipulating these systems in adulthood alters brain and behavior, so why should we consider oxytocin and vasopressin in the developmental emergence of brain and behavior?…”
Section: Introductionmentioning
confidence: 99%